2022
DOI: 10.1039/d2ta01890j
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of an AgPd nanoalloy with oxidation for formate oxidation electrocatalysis

Abstract: The emergence of heterointerfaces with two-dimensional oxide films grown on metal substrates have opened up a completely new opportunity for the development of energy conversion catalysts. However, the mechanism understanding...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 59 publications
2
8
0
Order By: Relevance
“…Additionally, Pd@PdPt NWs also reveal higher mass activity (1.3 A mg Pd −1 ) than Pd CC (0.19 A mg Pd −1 , Fig. S8†) and recently reported Pt and Pd-based electrocatalysts (Table 1), 7,17,19,20,45–48 confirming their high activity, again. Concurrently, the peak 1 potential of Pd@PdPt 0.024 NWs is negatively shifted by 0.16 V compared to that of the original Pd NWs, showing a smaller FOR overpotential.…”
Section: Resultssupporting
confidence: 78%
“…Additionally, Pd@PdPt NWs also reveal higher mass activity (1.3 A mg Pd −1 ) than Pd CC (0.19 A mg Pd −1 , Fig. S8†) and recently reported Pt and Pd-based electrocatalysts (Table 1), 7,17,19,20,45–48 confirming their high activity, again. Concurrently, the peak 1 potential of Pd@PdPt 0.024 NWs is negatively shifted by 0.16 V compared to that of the original Pd NWs, showing a smaller FOR overpotential.…”
Section: Resultssupporting
confidence: 78%
“…Palladium (Pd) and Pd-based electrocatalysts have gained special interests due to their durability and effectiveness in the electrooxidation of formate . Previous studies have shown that the electrooxidation of formate on Pd-based catalysts does not yield any carbonaceous poisoning species (i.e., CO ad , CH x ) in alkaline media, which is completely different from other carbon-based fuels. ,, Unfortunately, the adsorbed hydrogen (H ad ) on palladium sites, unlike the conventional carbonaceous poisoning species on noble metal catalysts, acts as a major adsorbed species and blocks the active sites of Pd during FOR. , To resolve this long-standing problem, several efforts have been made to modulate the property of Pd-based catalysts to facilitate the FOR process. In general, these attempts can be classified into two categories: (1) tuning the binding strength of hydrogen on active sites. For instance, different Pd alloys have been synthesized to optimize the hydrogen binding energy (HBE) on Pd active sites by shifting the d-band center of the materials, thus improving the activity of catalysts. , 2) introducing oxyphilic components to the surface of catalysts.…”
Section: Introductionmentioning
confidence: 99%
“…Direct formate fuel cells (DFFCs), in particular, as a promising energy conversion device, have the unique advantage of being easy to treat as solids or solutions. [ 5 ] Although appealing, the large scale commercialization of DFFCs has been seriously hindered by the low efficiency and sluggish reaction kinetics of the cathode reaction (oxygen reduction reaction, ORR) [ 6 ] and anode reaction (formate oxidation reaction, FOR), [ 7 ] resulting in the low power density and current density. Therefore, it is crucial to develop high efficiency and stable anode and cathode catalysts for DFFCs.…”
Section: Introductionmentioning
confidence: 99%